DEVELOPING SPEAKING SKILLS THROUGH CONVERSATION ACTIVITIES: A STUDY AT SMPN 44 BATAM - Putri, Aulia (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2025)
This study examined the use of conversation activities and how they improved the speaking skills of the eighth graders of SMPN 44 Batam in the academic year of 2024/2025. The research sought to find out how students fluently expressed themselves in vocabulary, pronunciation, and overall confidence with regards to speech through guided speaking activities. A qualitative approach was applied using triangulation in data collection which included classroom observation, semi-structured interviews with the teachers and students, and document analysis. The raw data were processed in a cyclical manner through data reduction, data display, and conclusion drawing during fieldwork. The findings showed that conversation activities greatly enhanced students' engagement with the speaking tasks, their confidence to express ideas, and general performance in speaking. It was shown that interaction among students and working in collaborative groups alleviated anxiety and promoted more genuine communication. The support of teacher’s prompt and accurate feedback was also important for the students' improvement. The conversation approach used in the study provides a good and interesting environment for teaching English. Sufficient practice to develop students' spoken English and communicative skills is provided to be used in real situations.